2022
DOI: 10.12659/msm.936614
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Focused Extracorporeal Shock Wave Therapy in Chronic Low Back Pain: A Prospective Randomized 3-Month Follow-Up Study

Abstract: Background Extracorporeal shock wave therapy (ESWT) is a modern physiotherapeutic method that is useful for treating musculoskeletal conditions. There are still limited data from well-designed studies evaluating the clinical efficiency of ESWT in low back pain (LBP). Therefore, this study aimed to assess the effectiveness of the focused ESWT (fESWT) in reducing pain and improving the functional status of patients with chronic LBP. Material/Methods The study involved 40 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…The studies by Walewicz et al 16 and Lee et al 17 also reported that ESWT can significantly reduce pain and improve the general functional state. However, a recent study by Rajfur et al 15 reported that ESWT has a role in reducing pain, but no significant effect on improving functional state. In our study, our results were consistent with the conclusions made by Zhang, Walewicz and Lee et al 17 The mechanism of action of the ESWT involves cell membrane destruction at the pain site as a result of the mechanical stress effect, cavitation effect and osmotic effect of the shock wave.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The studies by Walewicz et al 16 and Lee et al 17 also reported that ESWT can significantly reduce pain and improve the general functional state. However, a recent study by Rajfur et al 15 reported that ESWT has a role in reducing pain, but no significant effect on improving functional state. In our study, our results were consistent with the conclusions made by Zhang, Walewicz and Lee et al 17 The mechanism of action of the ESWT involves cell membrane destruction at the pain site as a result of the mechanical stress effect, cavitation effect and osmotic effect of the shock wave.…”
Section: Discussionmentioning
confidence: 98%
“…14 However, recent studies on the effect of ESWT combined with exercise have conflicting results on whether ESWT with exercise can effectively improve patients' functional state. [15][16][17] Therefore, the current study analyzes and compares the effects of extracorporeal shock wave and thermomagnetic therapy on pain relief and limb function improvement in the treatment of LBP, to provide more valuable reference for the clinical treatment of this disease.…”
Section: A H E a D O F P R I N Tmentioning
confidence: 99%
“…Fourteen studies, [9][10][11][12][13]15,18,19,[21][22][23][24][25]29] including 1242 patients, reported posttreatment ODI with significant heterogeneity (I 2 = 98%, P < .00001). The meta-analysis used a random-effects model, and the results showed that ESWT improved dysfunction better than the others (MD = −6.01, 95%CI [−7.97, −4.05], P < .00001).…”
Section: Oswestry Disability Index (After Treatment)mentioning
confidence: 99%
“…Five studies, [15,19,[21][22][23] including 209 patients, reported ODI at the 3-month follow-up, with moderate heterogeneity (I 2 = 70%, P = .01). The ODI of the experimental group remained lower than that of others according to a meta-analysis using a randomeffects model (MD = −5.95, 95%CI [−10.06, −1.84], P = .005).…”
Section: Oswestry Disability Index (Follow-up Of 3 Months)mentioning
confidence: 99%
See 1 more Smart Citation